2022
DOI: 10.3390/jcm11247499
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis Infections, Reinfections and Serological Response in a Large Italian Sexually Transmitted Disease Centre: A Monocentric Retrospective Study

Abstract: Background: Syphilis infection does not confer definitive and protective immunity against reinfection, and crucial aspects of repeated episodes of syphilis are far from being understood, especially among people living with HIV (PLWH). Methods: In order to explore the burden of syphilis in a large cohort of HIV-negative patients and PLWH, this retrospective study describes the demographics, clinical presentation and treatment outcome of patients with syphilis treated at our clinic from 2013 to 2021. Results: Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
3
7
0
Order By: Relevance
“…However, it is unknown whether and to what extent this could contribute to the differences observed between this study and the Grillová et al [18] syphilis TLR2 polymorphism study. HIV positivity could affect participants' distribution in the control group or case group, as HIV coinfection can cause serofast or non-responding serology [30]. Despite that, a low prevalence of HIV positivity and no discrimination between active and past infection in participants limit the effect of HIV coinfection in our study.…”
Section: Discussionmentioning
confidence: 83%
“…However, it is unknown whether and to what extent this could contribute to the differences observed between this study and the Grillová et al [18] syphilis TLR2 polymorphism study. HIV positivity could affect participants' distribution in the control group or case group, as HIV coinfection can cause serofast or non-responding serology [30]. Despite that, a low prevalence of HIV positivity and no discrimination between active and past infection in participants limit the effect of HIV coinfection in our study.…”
Section: Discussionmentioning
confidence: 83%
“…[1][2][3] Because previous infection does not prevent future episodes, 4 reinfection is not only possible but also frequent among high-risk populations. 5,6 It have been well documented in rabbit models that previous infections confer partial immunity for future exposure, expressed as less symptomatic infection or no infection after repeated T. pallidum inoculation. 7 Some studies in humans have reported that in repeat T. pallidum infections, the clinical presentation may be less symptomatic 8,9 or more frequently asymptomatic, 10,11 but others have found no differences in the clinical presentation of syphilis in repeat infections.…”
mentioning
confidence: 99%
“…Syphilis is a sexually transmitted infection (STI) caused by the bacterium Treponema pallidum , which remains a worldwide public health problem 1–3 . Because previous infection does not prevent future episodes, 4 reinfection is not only possible but also frequent among high-risk populations 5,6 …”
mentioning
confidence: 99%
“…Syphilis is a sexually transmitted infection, caused by the bacterial spirochete Treponema pallidum, although syphilis is curable with antibiotic treatment reinfections are possible. 3,4 Consistent with other spirochetes, direct detection of T. pallidum using available laboratory testing is challenging. Currently, case definitions for syphilis and other notifiable spirochetes use a combination of indirect detection methods to assess clinical and surveillance significance.…”
mentioning
confidence: 99%
“…Syphilis is a sexually transmitted infection, caused by the bacterial spirochete Treponema pallidum , although syphilis is curable with antibiotic treatment reinfections are possible 3,4 . Consistent with other spirochetes, direct detection of T. pallidum using available laboratory testing is challenging.…”
mentioning
confidence: 99%